2013
DOI: 10.1007/s00404-013-2815-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis about the influence on the fetus infected with parvovirus B19 using amniotic erythropoietin and troponin-T

Abstract: The study has determined an amniotic Epo level of ≥50 mU/ml as a factor of the influence on the fetus infected with PB19. The measurement of amniotic Epo level combined with amniotic TnT level is effective for determining the severity of fetal hypoxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Of the 896 articles identified through the search, 87 were assessed for their eligibility (Table S2) and 35 studies were eventually included in the systematic review (Figure and Table ). These 35 studies included 611 fetuses affected by PB19 infection based on serological or virological confirmation or presence of signs of fetal anemia, such as hydrops, on ultrasound in fetuses with infected mothers. The definition of fetal hydrops in each included study is reported in Table S3.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 896 articles identified through the search, 87 were assessed for their eligibility (Table S2) and 35 studies were eventually included in the systematic review (Figure and Table ). These 35 studies included 611 fetuses affected by PB19 infection based on serological or virological confirmation or presence of signs of fetal anemia, such as hydrops, on ultrasound in fetuses with infected mothers. The definition of fetal hydrops in each included study is reported in Table S3.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms of filtration (transport) of cardiospecific Tn molecules from the bloodstream to other biological fluids are not investigated, and, accordingly, these possibilities of non-invasive diagnostics have not been validated. Thus, the study of the metabolic pathway of cardiospecific Tns and potential factors influencing it is a relatively large and poorly studied area for further research that is needed to optimize diagnostics and validate new diagnostic capabilities( Stefanovic and Loukovaara, 2005 ; Zhu et al, 2007 ; Van Mieghem et al, 2010 ; Yoshida et al, 2013 ; Blohm et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Determination of erythropoietin in amniotic fluid is a useful investigation. However, other pathological conditions can contribute to aberrations in levels of amniotic erythropoietin (such as parvo virus B19 infection [3] and hypoxia [4]). …”
mentioning
confidence: 99%